The effect of visual-graphic tooth brushing teaching method on the plaque index of 8-year old pupils of Epifanio Delos Santos Elementary School - Correa, Maria Katrina Rosario O.; Gilbuena, Fatima Mae D.; Palileo, Raphael M.; Medina, Vicente III, O.
INTRODUCTION: Statistics show that 87.4% of the entire Philippine population and 75.7% of twelve-year-old Filipino children suffer from dental caries (NMEDS, 2011). This oral health condition in the country is alarming considering that dental caries is a preventable disease. Studies have shown the effectiveness of tooth brushing in caries reduction and plaque reduction (Okada et al, 2000) (Srivastava et al, 2013). It is therefore important that the proper tooth brushing technique be taught to children who are still in their formative years. This study aims to determine the effect of Visual-Graphic tooth brushing teaching method on the plaque indices of 8-year-old school children.
METHODS: Fourteen eight-year old grade three pupils of EDSES participated in the study. During the baseline phase, the plaque indices of the participants were measured before (base BT) and after toothbrushing (base AT). The following day (Intervention phase), a Visual-Graphic presentation of the Modified Bass tooth brushing technique was shown, and then the plaque indices were measured (interBT). They were then instructed to brush their teeth using the technique they have learned from the video, and their plaque indices were measured (interAT). Plaque indices were measured by an examiner dentist using the Turesky et al-Modified Quigley and Hein Plaque Index, The data obtained was subjected to paired t-test statistical analysis with a confidence interval of 95%, using the GNU PSPP software.
RESULTS: The results obtained from the experimental data of 14 participants (0.85 power) showed statistically significant difference and a general reduction for both the baseline (baseBT-baseAT; p-value= .0036) and intervention (interBT-interAT; p-value= .0031) plaque index scores before and after tooth brushing. To show the efficacy of the Visual-Graphic approach in teaching tooth brushing among the participants, the Mean Difference Plaque Indices for both the baseline (MDPI baseline) and intervention (MDPI intervention) data were compared. The comparison showed that the improvement in plaque indices after tooth brushing is higher for the intervention group than for the baseline group, with a statistically significant difference and a p-value of 0.0256. The reduction in plaque index could be taken to mean that the visual-graphic tooth brushing presentation was effective in teaching the pupils proper tooth brushing. The pupils may have adopted the correct tooth brush angulation and brushing strokes shown in the video, as observed in the improvement in plaque index.
CONCLUSION: This suggests that the Visual-Graphic teaching method in the form of a video is indeed an effective tool in the immediate reduction of plaque index among the 8-year old Grade Three pupils of EDSES.
KEYWORDS: tooth brushing, teaching methods, visual-graphic, plaque index.
Thesis (Doctor of Dental Medicine)--University of the Philippines Manila.
Keywords: Tooth brushing-Aids and devices; Visual graphic; Plaque index